2018
DOI: 10.2147/copd.s156121
|View full text |Cite
|
Sign up to set email alerts
|

The influence of disease severity and lifestyle factors on the peak annual 25(OH)D value of COPD patients

Abstract: BackgroundThe prevalence of individuals deficient in vitamin D (defined as a serum level of the stable metabolite 25(OH)D <50 nmol/L) is increasing in countries with low annual ultraviolet (UV) radiation and among individuals unable to perform outdoor activities, for example, COPD patients.ObjectiveTo assess the role of vitamin D deficiency, independently of seasonal variation, the peak annual value of 25(OH)D was measured in subjects with advanced COPD ± long-term oxygen therapy (LTOT) and lung healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…No previous Scandinavian [ 11 , 13 , 37 ] nor more recent international [ 22 , 33 ] study on patients with COPD have found a significant association between gender and vitamin D status. In contrast to our findings Black et al found a significantly higher level of 25(OH)D in men compared to women, 78.3 nmol/L versus 71.7 nmol/L, in a cohort from the Third National Health and nutrition Examination Survey (NHANES III) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…No previous Scandinavian [ 11 , 13 , 37 ] nor more recent international [ 22 , 33 ] study on patients with COPD have found a significant association between gender and vitamin D status. In contrast to our findings Black et al found a significantly higher level of 25(OH)D in men compared to women, 78.3 nmol/L versus 71.7 nmol/L, in a cohort from the Third National Health and nutrition Examination Survey (NHANES III) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in lifestyle, physical exercise and thereby also sunlight exposure presumably display key factors in the associations between 25-OHD levels and disease severity in COPD. As generally listlessness increases with pronounced pulmonary impairment, it is assumed that also light exposure decreases with disease progression, which in turn predisposes for vitamin D deficiency (7,19,50). In line with this, while the GOLD stage and weekly hours of sunlight exposure were not generally associated (Kruskal-Wallis test, P=0.051), patients in GOLD stage IV reported significantly lower weekly hours of sunlight exposure than those in GOLD stage I in direct comparison (Mann-Whitney test, P=0.022).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency, defined as serum-25(OH)D <50 nmol/ L, is associated with insufficient outdoor activities and dietary intake, and reflects COPD severity as previously shown. 33 To measure FEV 1 and FVC and to calculate the ratio of these volumes, dynamic spirometry was performed before and after bronchodilatation (spirometry was repeated ≥15 min after inhalation of salbutamol 0.6 mg) using Hedenström as a reference. 34,35 COPD was staged by airway obstruction, that is, FEV 1 % predicted 80-100%=GOLD stage I, 50-79% =stage II, 30-49%=stage III, and <30%=stage IV.…”
Section: Matched Controlsmentioning
confidence: 99%